2019
DOI: 10.1007/s00217-019-03373-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of pre-treatment and extraction conditions on the polyphenolic profile and antioxidant activity of Belgium apple wood

Abstract: This study describes the possibilities of valorising a waste stream that originates from apple wood by mapping the reducing capacity and phenolic profile from extracts derived from apple tree (Malus domestica). This study evaluated the efficiency of warm solvent extraction (WSE) and ultrasound-assisted extraction (UAE) techniques for extracting antioxidant phenolic compounds from the bark and core wood of an apple tree cultivated in the northeastern part of Belgium. Furthermore, the influence of the pre-treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…UAE of beech bark at 40 kHz frequency for 20 min, at 65 • C, using 70% ethanol as solvent led to a phenolic extract containing 72 mg GAE/g beech bark (169). Polyphenols, particularly phlorizin, have been obtained also from UAE of apple bark using 60% acetone (170).…”
Section: Lignocellulosic Byproductsmentioning
confidence: 98%
“…UAE of beech bark at 40 kHz frequency for 20 min, at 65 • C, using 70% ethanol as solvent led to a phenolic extract containing 72 mg GAE/g beech bark (169). Polyphenols, particularly phlorizin, have been obtained also from UAE of apple bark using 60% acetone (170).…”
Section: Lignocellulosic Byproductsmentioning
confidence: 98%
“…When the packaging films are used to cover fruits and vegetables, films with low solubility will be required in order to maintain their structural integrity. When the packaging films, especially edible films, are used to package candies and cakes, high solubility of the films can be better [ 7 , 11 , 19 , 21 ]. It was found that although the GPC films in this work became rubbery when they were immersed in water, they still maintained their structural integrity.…”
Section: Resultsmentioning
confidence: 99%
“…In nature, many animal and plant epidermis with antioxidant and antimicrobial properties were regarded as active packaging materials, such as crab and crawfish shell [5][6][7][8][9], fish skins [10], Polymers 2020, 12, 2310 2 of 22 apple tree bark [11] and mangosteen pericarp [12]. The main ingredient of shells of crustaceans, such as crab, shrimp and crawfish, is chitin, which is the second most abundant polysaccharide found in nature after cellulose [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, applewood contains significant amounts of bioactive compounds in the form of polyphenols, specifically in the classes of flavonoids, proanthocyanidins, and phenolic acids, which may supplant commonly used synthetic antioxidants in both foods and the pharmaceutical sector. To our knowledge, apart from our own studies [6][7][8][9], no other studies have focused on the extraction of bioactive compounds from applewood [10].…”
Section: Introductionmentioning
confidence: 99%